A MODEL OF THE SUPPLIER INVOLVEMENT IN THE PRODUCT INNOVATION - KUMAR, Manoj; RAMAN, Jyoti; RAMAN, Priya (Yugoslav Journal of Operations Research; Vol 27 No 1 (2017), 2016)
In this paper we examine the product innovation in a supply chain by a supplier and derive a model for a supplier’s product innovation policy. The product innovation of a supplier can contribute to the long-term competitiveness for the supply chain, and as it is for many supply chains a major factor, it should be considered in the development of strategies for a supplier. Here, we evaluate the effectiveness of supplier product innovation as a strategic tool to enhance the competitiveness and viability of supply chain. This paper explores the dynamic research performance of a supplier with endogenous time preference under a given arrangement of product innovation. We find that the optimal effort level and the achieved product innovation obey a saddle point path, or show tremendous fluctuations even without introducing the stochastic nature of product innovative activity. We also find that the fluctuation frequency is largely dependent both on the supplier’s characteristics such as supplier’s product innovative ability and on the nature of product innovation process per se. Short-run analyses are also made on the effect of supply chain cooperation in the product innovation process.